Keanekaragaman Jenis Amfibi untuk Mendukung Kegiatan Ekowisata di Desa Braja Harjosari Kabupaten Lampung Timur - Angga Arista; Gunardi Djoko Winarno; Rudi Hilmanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Amphibian life in nature is an interesting case which can be an ecotourism interest. The life cycle as well as the uniqe behaviours of the amphibi, is an interesting case to support the ecotourism activities. This research intends to determine the richness of amphibian minds, the diversity of amphibian kinds, and the amphibian distribution in order to support the ecotourism activities and to determine the society perception in utilizing the amphibi for the ecotourism activities. A combination of line transect method and Visual Encounter Survey method were used to know the species richness diversity and the distribution. One score one indicator quisioner was used to know the society perception against the amphibi to support ecotourism. The research was conducted in Braja Harjasari Village, East Lampung Regency during March to April 2017. Data analyzing was used a Shannon-wiener and Margalef index. The sosciety perception was analyzed descriptively and showed in a chart. The result showed that the amphibian richness was 0,6 which mean low, the diversity was 1,0 which meant medium, the shannon-wiener and margalef index was 0,9 which mean low community was stable and each kind of the amphibi was distributed equally. The society perception against the amphibi to support the ecotourism activities was mostly positive.